PEMBUATAN GAME ANDROID 2D PETUALANGAN MR.KENTANG MENGGUNAKAN UNITY - Dwi Kuncoro STMIK AUB Surakarta; Alvian Putra Mahardhika STMIK AUB (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2015)
ABSTRACT - Playing games is one way to relieve boredom and stress of everyday activities. Type of game more and more as the development of technology, from the desktop to the smartphone game. Android operating system to be one of the most popular mobile phone in the world today. From these circumstances the author tries to make an adventure game genre based on Android. This game can be used as an option to relieve boredom or just to fill the void in his spare time by playing games, and also to encourage the establishment of local game developers, which is still small compared with the foreign game developers. Groove design of the game is made of storyboard and then designed the depiction of the character, background and the game odds are bypassed by using CorelDraw X6. Depictions of the supporting elements of the game already completed later diterpakan the game engine. The game is built using C # programming language with Unity software. Results of this research have produced a game called